Voluntary Disclosure, Information Asymmetry, and Insider Selling through Secondary Equity Offerings* - MARQUARDT, CAROL. A.; WIEDMAN, CHRISTINE I. (Contemporary Accounting Research, 1998)
This paper examines the relation of voluntary disclosure of management earnings forecasts and information asymmetry to insider selling through secondary equity offerings. We hypothesize that the pattern of voluntary disclosure and level of information asymmetry prior to secondary equity offerings differs systematically based on the identity of the seller. Specifically, we predict a greater frequency of voluntary disclosure and decreased level of information asymmetry when managers sell their stock through a secondary offering. We examine this hypothesis in a cross‐sectional analysis of 210 secondary equity offerings from 1984‐91, using a two‐stage conditional maximum likelihood simultaneous equations estimation procedure, which allows for possible endogeneity in the manager's decision to sell stock. Consistent with our predictions, we document a significantly positive association between managerial participation and voluntary disclosure of earnings forecasts in the nine‐month period prior to registration of the offering. We also document a significantly negative association between managerial participation and two proxies for information asymmetry. The findings provide evidence that managers act as if reduced information asymmetry correlates with a reduced cost of capital.